Occupational segregation during the 1980s and 1990s: The case of Finnish manufacturing - Sami Napari (The Research Institute of the Finnish Economy (ETLA), 2005)
This descriptive paper investigates occupational segregation by gender during the 1980s and 1990s among white-collar workers in the Finnish manufacturing. Particular attention is paid to the relationship between education and segregation. Also the question how segregation evolves with work experience is analyzed. The results show that although occupational segregation has continuously declined, the level of segregation is still high. Occupational differences between men and women cannot be explained by relying on the gender differences in the educational background. The results also show that men and women segregate into different occupations already at the beginning of their careers, and the level of segregation realized at the entry moment is found to be enduring.
Keywords: J11; J16; J24; 330; occupational segregation; education; work experience; Verarbeitendes Gewerbe; Arbeitsmarktsegmentierung; Finnland; Geschlechterdiskriminierung